Adopting a Dual Strategy: Maximizing the Potential for Change - Taryana; Suprihartini, Yayuk (Escalate : Economics and Business Journal, 2024)
The article delves into the dynamics of strategic management within the context of PT. Tangerang Tirta Manunggal, examining the relationships among Force for Strategic Implementation (FSI), Information System Sophistication (ISS), External Factors (EF), and Performance Capability (PC). Utilizing a sample of 85 participants, the study employs Smart PLS analysis to scrutinize both direct and indirect effects. The results demonstrate significant direct impacts, with FSI positively influencing EF and PC, and ISS exerting a positive influence on EF. Furthermore, the study unveils meaningful indirect effects, indicating that the influence of FSI and ISS on PC is partially mediated by their impact on EF. These findings collectively underscore the strategic significance of well-implemented strategies and sophisticated information systems in shaping external factors and enhancing organizational performance capabilities. The insights provided are valuable for decision-makers seeking to navigate a dynamic business environment effectively.